IN SILICO CHARACTERIZATION, MOLECULAR DOCKING, AND IN VITRO EVALUATION OF TRIAZOLE DERIVATIVES AS POTENTIAL ANTICANCER AGENTS - T, HARSHITHA; KUMAR T, VINAY; T, VINEETHA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study was to perform in silico molecular docking and in vitro anticancer studies of proposed 1,2,4-triazole derivatives for the determination of their anticancer activity. Methods: A series of 10 triazole compounds with different substituents were drawn in ACD Lab ChemSketch software. Molecular and biological properties were identified using Molinspiration software. The compounds that obeyed Lipinski rule of five are subjected for pharmacokinetic parameters prediction and docking analysis. SwissDock ADME software is used for the prediction of absorption, distribution, metabolism, and elimination. Then, the compounds are docked with target enzymes in Chimera software 1.14 version. The molecular docking studies revealed favorable molecular interactions and binding energies. The compounds that showed good docking results were synthesized through wet lab synthesis and further preceded for in vitro anticancer studies. Results: Three compounds are selected for wet lab synthesis due to their good docking results compared to other compounds. The synthesized compounds are subjected to different in vitro anticancer studies and found to be having potential anticancer activity. Conclusion: The pharmacokinetic and docking studies conclude that the triazole compounds have potential as anticancer agents. The in vitro anticancer studies revealed that the triazole derivatives are having high potency of anticancer activity against pancreatic cell lines.